The effect of a savings intervention on women's intimate partner violence victimization: heterogeneous findings from a randomized controlled trial in Colombia - Margaret E. Tankard; Elizabeth Levy Paluck; Deborah A. Prentice (BMC, 2019)
Abstract Background Women's economic empowerment has long been assumed to lead to their social empowerment, but systematic tests of this relationship have only recently begun to appear in the literature. Theory predicts that control over resources, as through a savings account, may increase women's negotiating power and self-efficacy. In this way, "economic empowerment" may lead to "social empowerment," and have related benefits such as helping to reduce risk of intimate partner violence (IPV). The current study tests effects of an economic empowerment intervention on women's social empowerment, IPV victimization, and health. Methods We conducted an 18-month randomized controlled trial among 1800 urban poor women in Colombia between 2013 and 2015. The trial tested the impact of a savings account offer bundled with health services (vs. health services alone) on social empowerment outcomes, IPV victimization, and health. Results The bundled savings treatment did not have average effects on most outcomes, although it produced a small significant increase in financial participation and decrease in symptoms of depression. Treatment effects on perceived norms, decision-making patterns, self-reported IPV victimization, and health depended on whether women's partnerships were free of violence when they entered the trial; specifically, women in nonviolent partnerships at baseline showed more positive effects of the intervention. Conclusions Although bundling economic empowerment interventions with support features has been shown to empower poor women, this trial found that a bundled treatment did not on average improve most social and health outcomes of poor women experiencing IPV. Trial registration Registered retrospectively, prior to realization of outcomes, 5/29/14: Evidence in Governance and Politics #20140529AA.